A Study on the Spatio-Temporal Characteristics and Spatial Differentiation of the Development Efficiency of China’s Digital Cultural Industry - You, Denggui (Asia Pacific Economic and Management Review, 2025)
Under the national digital cultural strategy, it is crucial to systematically evaluate and continuously track the development efficiency of China’s digital cultural industry. This paper constructs a global super-efficiency EBM model that considers non-expected outputs, empirically measures the development efficiency of China’s digital cultural sector from 2011 to 2023, and uses the Moran index and Dagum Gini coefficient methods to comprehensively and deeply reveal the temporal and spatial characteristics and spatial differentiation of China’s digital cultural industry development efficiency. The study finds that: (1) The overall efficiency of China’s digital cultural industry is relatively low, with an average efficiency of 0.35, exhibiting a typical “V”-shaped distribution across different periods, and the eastern region significantly outperforms other areas. (2) The global Moran index shows a fluctuating downward trend overall, with a “Λ”-shaped distribution across different periods, and the local Moran index reveals that its spatial distribution is primarily concentrated in “H-H” and “L-L” clusters. (3) The overall disparities exhibit a fluctuating upward trend, with inter-regional disparities being the dominant factor, accounting for an average contribution rate of 38.50%. This study aims to promote the high-quality development of China’s digital cultural industry by providing valuable references for future policy-making and decision-making.